Marketing információs rendszerek az Egis Gyógyszergyár Zrt. gyakorlatában - Szőke Lászlóné (2015)
Choosing the topic of my degree thesis was inspired by my interest to the marketing activites. Another inspiration was that there were not any writings about the marketing informational system, resp. about the function of the Egis Pharmaceuticals. This area is waiting for discovery. This interest and the theoretical model laid by one of the biggest marketing authorities, Philip Kotler gave me the thought to map the marketing activities Egis Pharmaceuticals, according to the theoretical model. Every company, which would like to stay competitive under the marketing conditions, their essential activity is the marketing. At the Egis Pharmaceuticals, the marketing activities play an important role and according to that is has the biggest resources apparatus. The pharmaceutical marketing is said to be a special area, because it is different from general marketing. The efficiency of the successful marketing activities depends not only on the size of and skills of labour but ont he informational background connected to that as well. Before writing my diploma work I put more questions to myself. Can this theoretical model be used int the practice? Is this model working at the company or another model is present? If yes, is its function effective? In case of a diverse model, is there a similarity or we are speaking about another model? To answer my questions I carried out primer research as operative method in a form of an interview. When I was interviewing the international marketing manager who works int he company’s area I obtained some information which helped me to gain insight into the managers’ work. Besides with this method I managed to map the function of the company’s marketing informational systems. As a conclusion I am stating that the theoretical model is not working so at the company, like Kotler outlined. However, there are similarities, but because of the pharmaceutical specialisation some different parts can be discovered int he practical model. I think the Kolter-model coult show a direction for all companies while they are developing their marketing activities, but the companies continue other and other activities, produce other and other products and that is why each company have to form that to their own image.